Aural Abcesses in Eastern Box Turtles - Hoggard, Cheryl; McFarland, Melody (Wildlife Rehabilitation Bulletin, 2005)
Piedmont Wildlife Center (PWC) is currently in its second year of existence and has received more than 200 Eastern box turtles, Terrapene carolina carolina. Most of these animals are found after being hit by automobiles or lawnmowers. There are also a significant number that are found lethargic and unable to retract their heads due to large swellings on the head. Experienced wildlife rehabilitators immediately recognize this as an aural (ear) abscess, a relatively common affliction of box turtles. A study conducted at North Carolina State University (NCS) College of Veterinary Medicine, examined aerobic bacterial isolates from 23 injured or sick free ranging turtles brought to NCS for care prior to 2003. The NCS admissions and study occurred prior to the existence of PWC. Multiple microbial agents were cultured, which were generally found to be opportunistic Gram–negative bacteria. Of the 23 cultures obtained, the most commonly isolated organisms were Proteus vulgaris (N=5), Escherichia coli (N=5), and Aeromonas hydrophila (N=5) (Willer et al 2003). The intention of this paper is to provide an overview of this condition and the common bacteria associated with aural abscesses, and to supply a general understanding of how this condition relates to the anatomy of the ear. PWC is continuing the study begun at NCS with turtle aural cultures in an effort to better understand the possible causes of the abscesses. The hope is to eventually discern why wild turtles develop these abscesses and methods to decrease the incidence.